Preliminary Design and Simulation of a Turbo Expander for Small Rated Power Organic Rankine Cycle (ORC) - Roberto Capata; Gustavo Hernandez (Energies, 2014)
Nowadays, the Organic Rankine Cycle (ORC) system, which operates with organic fluids, is one of the leading technologies for “waste energy recovery”. It works as a conventional Rankine Cycle but, as mentioned, instead of steam/water, an organic fluid is used. This change allows it to convert low temperature heat into electric energy where required. Large numbers of studies have been carried out to identify the most suitable fluids, system parameters and the various configurations. In the present market, most ORC systems are designed and manufactured for the recovery of thermal energy from various sources operating at “large power rating” (exhaust gas turbines, internal combustion engines, geothermal sources, large melting furnaces, biomass, solar, etc.); from which it is possible to produce a large amount of electric energy (30 kW ÷ 300 kW). Such applications for small nominal power sources, as well as the exhaust gases of internal combustion engines (car sedan or town, ships, etc.) or small heat exchangers, are very limited. The few systems that have been designed and built for small scale applications, have, on the other hand, different types of expander (screw, scroll, etc.). These devices are not adapted for placement in small and restricted places like the interior of a conventional car. The aim of this work is to perform the preliminary design of a turbo-expander that meets diverse system requirements such as low pressure, small size and low mass flow rates. The expander must be adaptable to a small ORC system utilizing gas of a diesel engine or small gas turbine as thermal source to produce 2–10 kW of electricity. The temperature and pressure of the exhaust gases, in this case study (400–600 °C and a pressure of 2 bar), imposes a limit on the use of an organic fluid and on the net power that can be produced. In addition to water, fluids such as CO2, R134a and R245fa have been considered. Once the operating fluids has been chosen, the turbine characteristics (dimensions, input and output temperature, pressure ratio, etc.) have been calculated and an attempt to find the “nearly-optimal” combination has been carried out. The detailed design of a radial expander is presented and discussed. A thermo-mechanical performance study was carry out to verify structural tension and possible displacement. On the other hand, preliminary CFD analyses have been performed to verify the effectiveness of the design procedure.